1989
DOI: 10.1590/s0074-02761989000300019
|View full text |Cite
|
Sign up to set email alerts
|

Leishmaniose en Bolivie: IV. Le chien dans les cycles des leishmanioses en Bolivie

Abstract: En Bolivie le chien domestique est impliqué dans le cycle de la leishmaniose viscérale (Leishmania (Le.) chagasi) das les Yungas (alt. 1,000-2,000 m) et aussi dans le cycle de la leishmaniose tégumetaire (Le. (V.) braziliensis) dans l'Alto Beni (alt. 400-600 m). Mais il joue un rôle différent dans les deux cycles. Il est le prencipal résevoir, peut-être l'unique de Le. (Le.) chagasi dans les Yungas, et la source de contamination de l'home. Dans l'Alto Beni, il n'est seulement qu'une victime, comme l'home, de L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The two species of two-toed sloths, Choloepus didactylus and C. hoffmanni, are the only extant representatives of the Megalonychidae (Adam, 1999), occurring in partial sympatry in the Andean regions and western Amazonia (Le Pont and Desjeux, 1992;Emmons and Feer, 1997;Adam, 1999;Eisenberg and Redford, 1999). Although their distributions are reasonably well-understood on a broad scale, the precise boundaries of their ranges are still unresolved.…”
Section: Cristiano Trapé Trinca Francesca Belem Lopes Palmeira José Dmentioning
confidence: 99%
“…The two species of two-toed sloths, Choloepus didactylus and C. hoffmanni, are the only extant representatives of the Megalonychidae (Adam, 1999), occurring in partial sympatry in the Andean regions and western Amazonia (Le Pont and Desjeux, 1992;Emmons and Feer, 1997;Adam, 1999;Eisenberg and Redford, 1999). Although their distributions are reasonably well-understood on a broad scale, the precise boundaries of their ranges are still unresolved.…”
Section: Cristiano Trapé Trinca Francesca Belem Lopes Palmeira José Dmentioning
confidence: 99%
“…In the "Yungas" valleys cutaneous and mucocutaneous leishmaniasis constitute a serious public health issue, since consequences for the infected patients are severe mutilations, mostly located on their face (Le Pont et al 1992). In this area, a prevalence of around 20% was reported based on observation of active lesions and scar without differences according to sex (Le Pont et al 1992).…”
mentioning
confidence: 99%
“…In North and South Yungas provinces (corresponding to the studied area) 353 cases of cutaneous and muco-cutaneous leishmaniasis have been registered in 2001 (report of the SNIS, Ministerio de Salud, Bolivia). Whereas parasites belonging to Leishmania (Leishmania) amazonensis were scarcely identified (Desjeux et al 1987, Le Pont et al 1992, Dedet 1993), a recent study had revealed a new restricted focus due to L. (L.) amazonensis ) in a Yungas valley characterized by a severe dry season. The strain of the first case of human visceral leishmaniasis was identified without a doubt by isoenzyme as Leishmania (L.) chagasi ).…”
mentioning
confidence: 99%
“…22 All parasite isolates that have been characterized to species have primarily been reported in the north, center, and east of the country (i.e., Departments of La Paz, Beni, Pando, Santa Cruz, and Cochabamba) ( Figure 1 ). [16][17][18][19][20][21][22][23][24][25][26][27][28][29] Leishmania (L.) infantum , the causative agent of VL, was isolated from or detected in patients, [31][32][33] dogs, 34,35 and the insect vector Lutzomyia longipalpis 36 in the Yungas region in the Department of La Paz. To our knowledge, VL remains rare in Bolivia and is restricted to this unique focus in the Yungas region in the Beni department, where the first autochthonous case was diagnosed in 1984.…”
Section: Disease Distribution Notification and Incidencementioning
confidence: 99%
“…44,[48][49][50] Natural Leishmania infections have been found in a range of non-human mammal hosts (principally marsupials, rodents, edentates, and carnivores). 34,35,[51][52][53] However, their importance in the Leishmania transmission cycle in Bolivia is difficult to assess, because their role as reservoirs was not specifically studied. As previously shown in other eco-epidemiologic settings, 54 reservoir incrimination is difficult because it often is specific to the local epizoologic context and depends on a range of parameters (e.g., host abundance and distribution, infectiousness to the sandfly vector).…”
Section: Disease Distribution Notification and Incidencementioning
confidence: 99%